A revision of the living Mactridae (Bivalvia: Autobranchia) from Northern Argentina and Uruguay - Signorelli, Javier Hernan (2012)
Living bivalves of the family Mactridae from Northern Argentina and Uruguay are herein revised. A bibliographical research yielded 22 nominal species reported from this area. Material from several institutions as well as fi eldwork from La Paloma, Uruguay to San Blas, Argentina was studied. In addition, all type material were illustrated and redescribed. Descriptions of the soft and hard parts including ultrastructure of the shell, hinge and ligament using the Scanning electronic microscope (SEM) were carried out. We consider Mactra guidoi Signorelli and Scarabino, 2010, Mactra isabelleana d ́Orbigny, 1846, Mactra marplatensis Doello-Jurado, 1949, Mactra petitii d ́Orbigny, 1846 , Mactrella janeiroensis (Smith, 1915), Raeta plicatella (Lamarck, 1818) and Darina solenoides (King, 1832) as valid species. In addition, a list of synonyms as well as the corroborated distribution is proposed for each species.